Dual effects of (þ)-catechin on hemin-induced oxidative reactions: A potential pharmacological implication - Lu, Nai-Hao; He, Ying-Jie; Chen, Chao; Tian, Rong; Xiao, Qiang; Peng, Yi-Yuan (Free Radicals and Antioxidants)
Introduction: Although the anti- and pro-oxidant properties were the well-known phenomenons for flavonoids, the influence of flavonoids on free heme-dependent redox reactions was not definitely elucidated. Methods: By spectrophotometry and Western blotting, the influence of (þ)-catechin (a polyphenol identified in red wine, tea, and cocoa) on hemin-induced oxidative reactions was investigated in this study. Results: (þ)-Catechin was found to act as an efficient reducing agent for the reduction of ferryl heme to ferric state, demonstrating novel anti-oxidant pathway. However, this antioxidant had the ability to trigger hemin oxidation through producing additional hydrogen peroxide (H2O2). On the other hand, the effects of (þ)-catechin on hemineH2O2einduced protein (or methylene blue) oxidation depended on the concentrations of H2O2 and antioxidant. (þ)-Catechin exerted significant anti-oxidant ability when lower concentration of H2O2 was used. However, in the presence of higher concentration of H2O2, (þ)-catechin at low concentrations could significantly aggravate oxidative reactions and exhibit protective effects at high concentrations. Conclusions: The anti- and pro-oxidant effects of catechin on heme-dependent redox reactions at different concentration, may provide new insights into the dietary intake and therapeutic implications of catechins with free heme and heme proteins.
Keywords: Hemin; (þ)-Catechin; Oxidative reactions; Anti-oxidant; Pro-oxidant